Ask Question
14 October, 19:57

What is the answer?

5x - (x-11) = 21-6x

0
Answers (2)
  1. 14 October, 20:27
    0
    Answer: x=1

    Step-by-step explanation:

    Step 1: Simplify both sides of the equation.

    5x - (x-11) = 21-6x

    5x+-1 (x-11) = 21-6x (Distribute the Negative Sign)

    5x+-1x + (-1) (-11) = 21-6x

    5x+-x+11=21-6x

    5x+-x+11=21+-6x

    (5x+-x) + (11) = -6x+21 (Combine Like Terms)

    4x+11=-6x+21

    4x+11=-6x+21

    Step 2: Add 6x to both sides.

    4x+11+6x=-6x+21+6x

    10x+11=21

    Step 3: Subtract 11 from both sides.

    10x+11-11=21-11

    10x=10

    Step 4: Divide both sides by 10.

    10x/10 = 10/10
  2. 14 October, 21:51
    0
    1

    Step-by-step explanation:

    5x - (x-11) = 21-6x

    5x-x+11=21-6x

    4x+11=21-6x

    4x - (-6x) + 11=21

    4x+6x=21-11

    10x=10

    x=10/10

    x=1
Know the Answer?
Not Sure About the Answer?
Get an answer to your question ✅ “What is the answer? 5x - (x-11) = 21-6x ...” in 📙 Mathematics if there is no answer or all answers are wrong, use a search bar and try to find the answer among similar questions.
Search for Other Answers